Philology – the Art of Memory: On Stanisław Wyspiański’s Digital Archive - Popiel, Magdalena (Przestrzenie Teorii, 2024)
The paper discusses the issue of new philology in the context of the project of Stanisław Wyspiański’s Digital Archive. Inspired by projects by Jerome McGann and John Bryant (Rossetti Archive and Melville Electronic Library), the author considers the motivations behind and the benefits of such a venture. Wyspiański’s multimediality and dynamicity of the creative process suspending finality encourage the use of digital tools in academic research and educational activities related to his works. An analysis of Wyspiański’s creative process – a writer, painter, man of the theater – can reveal a complex, heterogenous simultaneity of his artistic activities.